Finite element investigation on the behaviour of structural steel beams subjected to standard & parametric fire - Kada, Abdelhak (2017)
This paper intends to present an investigation of the behaviour of steel beams under high temperatures rise due to fire using finite elements simulations with ANSYS software. Cases of study for solid as well as open web beams are considered and take into account uniform and transient temperature rise, material and geometric non-linear behaviour. Input fire scenarios are standard temperature-time curve ISO834 and parametric compartment fire model based upon Eurocode EN 1991-1-2. For the latter a comparison is made using the experimental results from BRE-Cardington tests data. Thermal and mechanical analysis is done using the effect of temperature dependent material properties and the Eurocode recommendations in estimating reduction mechanical steel properties. Three types of cellular beams are studied and the number of cells is shown to be critical for their behaviour under fire conditions. Results are related to temperature profiles in steel beam cross-sections, variation of displacements with respect to temperature change and critical temperatures.